Penyuluhan dan Pelatihan Pembuatan Moringa Dimsum, Produk Nutrasetikal sebagai Antihiperlipidemia - Ahmad Izzuddin; Reza Putri Oktavia; Mujtaba Alfan Nur; Ryan Wahyu Wijayanto (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
Hyperlipidemia is one of the non-communicable diseases which is the top 10 leading causes of death globally. The prevalence of hyperlipidemia in Indonesia in the 25-34 year age group is 9.3% and in the 55-64 year age group it has increased to 15.5%. The geographical conditions of Karangnongko Village are favorable for the growth of Moringa plants, so that many Moringa plants grow in residents' yards. For this reason, the KKM 135 team at UIN Maulana Malik Ibrahim Malang held counseling and training activities for women from the PKK driving team to improve the health status of the Karangnongko village community by making nutraceutical products Moringa dimsum. This activity is carried out using lecture methods, discussions, and direct practice through training. The results of community service activities show that the community does not know about hyperlipidemia. With counseling and training in the manufacture of nutraceutical products, the public knows more about hyperlipidemia and nutraceutical products as new innovations. After being given the material, the community began to understand hyperlipidemia and the nutraceutical product Moringa Dimsum as a way to prevent it.